Korean Version of Mini Mental Status Examination for Dementia Screening and Its' Short Form - Kim, Tae Hui; Jhoo, Jin Hyeong; Park, Joon Hyuk; Kim, Jeong Lan; Ryu, Seung Ho; Moon, Seok Woo; Choo, Il Han; Lee, Dong Woo; Yoon, Jong Chul; Do, Yeon Ja; Lee, Seok Bum; Kim, Moon Doo; et al. (Psychiatry investigation, 2010)
We developed a Korean version of Mini-Mental Status Examination (MMSE) optimized for screening dementia (MMSE-DS) and its' short form (SMMSE-DS). We constructed the MMSE-DS using the items of the two current Korean versions of MMSE and then construct the SMMSE-DS consisted of 13 items from the MMSE-DS based on the diagnostic accuracy of individual items for dementia. We investigated reliability and validity of MMSE-DS and SMMSE-DS on 1,555 subjects (1,222 nondemented controls, 333 dementia patients). We compared the diagnostic accuracy of the SMMSE-DS with that of the three full Korean versions of MMSE, and examined its' age- and education-specific optimal cutoff scores for dementia. The internal consistency obtained by Cronbach's coefficient alpha was 0.826. The inter-rater reliability and test-retest reliability were 0.968 (p<0.001) and 0.825 (p<0.001), respectively. It showed significant correlation with the Clinical Dementia Rating (CDR) (r=-0.698, p<0.05) and the three full Korean versions of MMSE (r=0.839-0.938, p<0.001). The area under the receiver operator curve for dementia of the SMMSE-DS was larger than those of the three full Korean versions of MMSE (p<0.001). Age, education and gender explained 19.4% of the total variance of SMMSE-DS scores. The optimal cutoff scores for dementia of the SMMSE-DS were estimated differently by age and educational attainment of the subjects. The SMMSE-DS was found to be accurate, brief and portable instrument for screening dementia in Korean elders, and may be particularly useful for screening dementia in elderly populations with wide variation in educational levels.